2016
DOI: 10.4103/2231-0762.178750
|View full text |Cite
|
Sign up to set email alerts
|

A survey on oral hygiene methods practiced by patients attending Dentistry Department at a Tertiary Care Hospital from Central Gujarat

Abstract: Objective:Oral hygiene is important not only for maintaining health of teeth and gingivae in an individual but also for good and uneventful regeneration and healing of tissues, when one has undergone one or other dental treatments. This makes it important to have an understanding of oral hygiene practices employed by the population.Materials and Methodology:This descriptive cross-sectional hospital-based survey was carried out to know oral hygiene methods practiced by patients who visited Department of Dentist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Majority of the adolescents brushed their teeth once daily. This is similar to the findings reported by Logaranjani et al 19 and Goryawala et al 23 To maximize the oral health, the American Dental Association (ADA) and US Surgeon General recommend that individuals should brush twice and floss at least once a day and have regular prophylactic dental visits. 24 The habit of brushing the teeth twice daily needs to be inculcated among the adolescents.…”
Section: Discussionsupporting
confidence: 87%
“…Majority of the adolescents brushed their teeth once daily. This is similar to the findings reported by Logaranjani et al 19 and Goryawala et al 23 To maximize the oral health, the American Dental Association (ADA) and US Surgeon General recommend that individuals should brush twice and floss at least once a day and have regular prophylactic dental visits. 24 The habit of brushing the teeth twice daily needs to be inculcated among the adolescents.…”
Section: Discussionsupporting
confidence: 87%
“…[ 12 ] Brushing after every meal and also before going to sleep at nights is very helpful in the prevention of dental diseases. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in the western part of India, by Goryawala S N et al, in 2015-2016, showed that 7% of the study participants used ayurvedic toothpaste and 3.5% used ayurvedic tooth powders. It was also observed that 3.1% of the participants used datun or chewing sticks [18].…”
Section: Indus Valley Civilization and Ancient Indian Civilization (Hmentioning
confidence: 98%